Implementation of Digital Marketing and Product Development to Increase Buyer Attraction in Pawon Encus MSMEs - Lailla, Nur (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: The aim of this research is to increase the understanding of MSME owners regarding optimizing digital marketing so they can develop their business. Design/Method/Approach: This research uses observation and interview methods (qualitative). Research Finding: The results of implementing Digital Marketing and developing Pawon Encus MSME business products are able to increase buyer attraction. Research limitation: The limitation of this research is the lack of time for sampling because MSME product owners are very difficult to find.